Risks and Benefits of Surgical Excision of Orbital Cavernous Venous Malformations (So-Called Cavernous Hemangioma): Factors Influencing the Outcome. Issue 3 (May 2021) - Strianese, Diego; Bonavolontà, Giulio; Iuliano, Adriana; Mariniello, Giuseppe; Elefante, Andrea; Liuzzi, Raffaele
Abstract : Purpose: To assess risks and benefits associated with surgical excision of orbital cavernous venous malformation and analyze factors influencing the outcome. Methods: Design: cohort study. Participants: 164 consecutive patients undergoing surgical removal of orbital cavernous venous malformation. Intervention: lateral or anterior orbitotomy. Outcome measures: visual acuity, visual field, pupillary function, ocular motility, and fundus examination. Influence of the mass volume and tumor location on the outcome was evaluated. The threshold value and risk group for the volume were evaluated using the receiver operating characteristic analysis; 8 orbital different quadrants, extraconal/intraconal position, and orbital apex extension were considered as variables to evaluate the location. Results: Postoperatively overall visual acuity ( p = 0.0084), visual field ( p < 0.0001), diplopia ( p < 0.0001), proptosis ( p < 0.0001), ocular motility ( p = 0.02), ptosis ( p = 0.033), choroidal fold ( p < 0.0001), disk edema ( p = 0.0004) were significantly improved. The commonest location was the lateral quadrant (28%). Choroidal folds were associated with tumor greater than 1100 mm 3 ( p = 0.001). Visual loss occurred in 2 patients (1.2%) and tonic pupil in 5 (3%, ) Visual deterioration was associated with the apical extension ( p = 0.001). Pupil efferent defect was associated with lateral quadrant location ( p = 0.011) and apical extension ( p = 0.05). Conclusions: Surgical removal of orbital cavernous venous malformation is a useful treatment modality, particularly for large size tumors. Removal of cavernous venous malformations located at the lateral aspect of the orbit carries an increased risk of permanent tonic pupil. Postoperative blindness is rarely seen and is often associated with the apical extension. Tailoring the surgical approach, depending on the relative position to the optic nerve, may have an important bearing on outcome. Abstract : Surgical excision through orbitotomy is a valid treatment option for orbital cavernous venous malformation. A careful preoperative evaluation to assess the risk benefit/ratio is however highly recommended.